THE POLITICS OF ISLAMIC LAW AND GENDER; WOMEN'S CONTESTATION IN THE ELECTION MAP IN BANTEN PROVINCE - Pitrotussaadah, Pitrotussaadah; Syafei, Zakaria; Chaerina, Nina; Fazri, Sultan Isnansyah (Universitas Islam Negeri Imam Bonjol Padang, 2024)
Women presently lead 37.5 percent of districts/cities in Banten Province. Additionally, in the previous government position, the figure reached 50%. Similarly, women won two elections at the provincial level in the four gubernatorial polls that were held. The substantial participation of women in Banten's election campaign is fascinating to investigate. This research aims to determine the contestation of women in the Political Islamic law and gender in Banten Province, as well as a review of Islamic law political on women's contestation in election political maps. This study employs a qualitative method of content analysis. This study's findings reveal that women's engagement in the political map of the regional election in Banten was due to the freedom, opportunity, and chance for women to participate in the political sphere. Furthermore, the family's involvement and participation were significant owing to their typical family background as politicians who previously served in the same position, known as the relay and inheritance of family leadership. Some refer to it as a familial political dynasty. According to an examination of Islamic law, women's participation in the political map of the regional elections in Banten does not contravene the siyasa syar'iyyah because it is included in the siyasa dusturiyyah. Furthermore, Islam does not forbid women from participating in politics